Upaya Peningkatan Hasil Belajar Biologi Siswa SMA Zion Makassar Kelas X IPA Melalui Model Pembelajaran Cooperative Learning Tipe Jigsaw pada Materi Klasifikasi Makhluk Hidup Tahun Pelajaran 2017/2018 - Jonathan, Demitrius (Biology Teaching and Learning, 2019)
Abstract.This research was discussing the importance of improving the quality of the process and learning outcomes through various optimal learning models, while the teacher holds a very important role in involving students who take learning. The purpose of this study was to improve the learning outcomes of Zion High School students through the jigsaw cooperative learning model in biology subjects for the academic year 2017/2018. This research is a Classroom Action research, which discusses student factors, teacher factors and student learning outcomes. The location of this study was in Zion Makassar High School, 30th grade science as many as 30 students in the even semester of the academic year 2017/2018. Implementation of the action consists of 3 (three) cycles followed by Observation and Reflection activities. Cooperative learning type jigsaw can improve student learning outcomes. Cooperative learning type jigsaw learning is very positive, and student learning outcomes increase each cycle.Keywords: biology learning outcomes, type jigsaw cooperative learning.